(untitled) (Research, Society and Development, 2021)
The grasshopper and the mane-lean are secondary pests of occasional, cyclical appearances and survival linked to several cultures of economic importance and that when found in large population levels can cause strong defoliation in the plantations. Therefore, the objective of this work was to evaluate the efficiency of the Metarril (Metarhizium anisopliae) and Boveril (Beauveria bassiana) compared to the insecticide Decis 25 EC in the control of grasshopper and mané-thin in the municipality of Oeiras-PI in different dosages. The experimental design used was a randomized block (DBC) with six treatments and six repetitions each. The treatments are: T1 - Witness (water application); T2 - Decis 25 EC (Deltamethrin), in a dose of 150 ml.ha¹; T3 - M. anisopliae 750 g.ha¹ (100%); T4 - M. anisopliae 375 g.ha¹ (50%); T5 - B. bassiana 750 g.ha¹ (100%) and T6 - B. bassiana 375 g.ha¹ (50%). The mycoinsecticides Boveril (B. bassiana) and Metarril (M. anisopliae), as well as the chemical insecticide Decis 25 EC showed efficiency in combating grasshoppers in the phase of nymph and mané-thin in pastures in the semi-arid region of Piauí, because it causes death most of the insects subjected to the test, thus reducing their population.